Fecal Microbiota and Its Correlation With Fatty Acids and Free Amino Acids Metabolism in Piglets After a Lactobacillus Strain Oral Administration - Zhang, Dongyan; Liu, Hui; Wang, Sixin; Zhang, Wei; Wang, Jing; Tian, Hongwu; Wang, Yamin; Ji, Haifeng (Frontiers in Microbiology, 2019)
Lactobacillus has a positive effect on the host intestinal microbiota. In piglets, dietary supplementation with Lactobacillus affects general health and plays an important role in nutrient digestion and fermentation. However, this association requires further investigation. Here, we studied newborn piglets from 12 litters. The nursed piglets were given a creep feed beginning on day 10 post-partum and weaned at day 30. Piglets were fed either a control basic diet or a diet including supplementation with Lactobacillus reuteri ZLR003 at 6.0×106 cfu/g feed. At day 30 and 60, feces samples were taken and used for sequencing of the V3-V4 hypervariable region of the 16S rRNA gene. At day 60, feces samples and serum samples were also taken and used to measure the short chain fatty acids (SCFAs) and to detect long chain fatty acids (LCFAs) and free amino acids (FAAs), respectively. The results revealed that L. reuteri ZLR003 could improve piglet fecal microbiota composition, especially at the end of weaned period. The concentrations of lactic acid and butyric acid in feces were higher, and acetic acid concentration was lower in the L. reuteri ZLR003 group compared with the control group (P < 0.05). The serum polyunsaturated fatty acids C18:2n6c, C18:3n3, C20:4n6, and C22:6n3 were significantly higher (P < 0.05), as were the serum free amino acids Gly, Ala, Val, Iso, Asn, Asp, Glu, Met, Phe, and Leu (P < 0.05), in the L. reuteri group compared with the control group. A correlation analysis revealed that the genera Ruminococcaceae_UCG-010 and Ruminococcaceae_UCG-014 had a negative correlation with the SCFAs content in feces, the genus Prevotella_9 had a higher positive correlation with C18:2n6c, and the genera Megasphaera and Mitsuokella had a more positive significant effect on the serum FAAs content in weaned piglets in the L. reuteri ZLR003 group compared with the control group. In conclusion, L. reuteri ZLR003 influenced the fecal microbiota composition of piglets, and its effects were related to the metabolism of SCFAs, LCFAs, and FAAs. Our findings will help facilitate the application of Lactobacillus strains in pig production.